Effect of Lactobacillus sp. probiotics on intestinal histology, Escherichia coli in excreta and broiler performance - Hidayat, M.N.; Malaka, R.; Agustina, L.; Pakiding, W. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The study was conducted to determine the effect of Lactobacillus sp. in intestinal histology, total amount of Escherichia coli in broiler chicken excreta and broiler performance. Research has been conducted using a completely randomized design with 4 treatments and 5 replications utilize 15 chickens. Lactobacillus sp. 5.8 x 107 CFU/mL was mixed in drinking water and also feed commercial concentrates together ad libitum. The results showed that treatment had significant effect (P <0.05) on weight gain, ration conversion, and final weight. There was no difference (P>0.05) ration consumption on doses of Lactobacillus sp. treatment 0 mL/days, 1 ml/days, 3 ml/days, and 5 ml/days. In general, the probiotic treatments of 1, 3, and 5 mL/days of lactobacillus sp. were better at villus height, villus surface area, weight gain, final weight, and feed conversion compared to control. Treatment a dose of 3 mL / d (1.7 x 108 CFU) is the best dose in providing optimal response to histology of the small intestine, and broiler performance. Treatment 5 mL/days has the lowest amount of Escherichia coli in manure of broiler. In conclusion, Lactobacillus sp. can be used as one candidate probiotic for broiler.